Kecerdasan Tradisional Untuk Kajian Kebencanaan Dalam Perspektif Hermeneutika - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2008)
The aim of this article is to identify the local genius related to disaster problems in hermeneutics perspective. Method used in this article is inductive and deductive analysis with analogical thinking and comparative thinking. Results of the analysis are a signal or early warning by local wisdom about environmental hazards. That is "the market was loss of its echo, the river was loss of its pool, the mountain was loss its mist". Sawo-kecik, kelor and jarak is crops used to protect against thunder. Curved gate as Plengkung Nirbaya (Curved Gate of Loss of Hazard) can be used to shelter against gale. The use of textile on every pillar of old houses is to mitigate against earthquake disaster in order that old houses can not collapse. There was be warning about to prevent against morale hazard and moral hazard in "Serat Wulang Reh" (Poetry ofWulang Reh).